A Morphological Analysis of Compound Words Exist in Kamala Harris’s Democratic National Convention Speech 2024 - Zahra Sabrina Maussa; Dewi Wulan Sari (Asosiasi Dosen Muda Indonesia, 2026)
Compounding is one of the word formation processes, it produces new meanings by combining two or more existing words. The resulting word is known as a compound word. The researcher conducted this research with Kamala Harris’ speech at Democratic National Convention in 2024 as the source of data. The objective of this research is to find out the compounding processes of English compound words used in Kamala Harris's speech at the Democratic National Convention in 2024, using Bauer’s theory. This research used qualitative descriptive method. The result of this research shows that the researcher found 51 data of compounding processes, which are contained in 3 types of compounding. These 3 types of compounding include 34 data from compound nouns, 12 data from compound adjectives, and 5 data from other form classes. In addition, this research did not identify any compounding processes for compound verbs, compound adverbs, rhyme-motivated compounds, or ablaut-motivated compounds.